2014
DOI: 10.5194/acp-14-8449-2014
|View full text |Cite
|
Sign up to set email alerts
|

A case study of aerosol scavenging in a biomass burning plume over eastern Canada during the 2011 BORTAS field experiment

Abstract: Abstract. We present measurements of a long-range smoke transport event recorded on 20-21 July 2011 over Halifax, Nova Scotia, Canada, during the Quantifying the impact of BOReal forest fires on Tropospheric oxidants over the Atlantic using Aircraft and Satellites (BORTAS-B) campaign. Ground-based Fourier transform spectrometers and photometers detected air masses associated with large wildland fires burning in eastern Manitoba and western Ontario.We investigate a plume with high trace gas amounts but low amou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…7a, with several highaltitude (∼ 7 km) samples having fairly low excess organic aerosol, but significant CO (300 ppbv). This trend is featured in Franklin et al (2014) where the high-altitude plume showed evidence of an aerosol rainout event causing low OA / CO ratios within the plume transected at those high altitudes.…”
Section: Net Production/loss Of Organic Aerosol With Timementioning
confidence: 93%
See 1 more Smart Citation
“…7a, with several highaltitude (∼ 7 km) samples having fairly low excess organic aerosol, but significant CO (300 ppbv). This trend is featured in Franklin et al (2014) where the high-altitude plume showed evidence of an aerosol rainout event causing low OA / CO ratios within the plume transected at those high altitudes.…”
Section: Net Production/loss Of Organic Aerosol With Timementioning
confidence: 93%
“…This ensured highgas, low-aerosol sampling periods were not included in the size-distribution analysis. At least one case of this situation in BORTAS-B has been attributed by Franklin et al (2014) to aerosol rainout during transport. The mean background concentrations for both BC number and OA mass were minimal (< 20 cm −3 and 2 µg m −3 , respectively).…”
Section: Plume Criteriamentioning
confidence: 99%
“…During the IPY (International Polar Year) in 2008, different Lagrangian studies (e.g., Roiger et al, 2011;Sodemann et al, 2011;Matsui et al, 2011) identified several Asian pollution plumes transported to the Arctic after a strong uplift in WCBs located over the Russian east coast and subsequently transported to the Arctic. Franklin et al (2014) and Taylor et al (2014) have documented the impact of wet removal in Canadian biomass burning plumes and confirmed that wet deposition is the dominant mechanism for BC removal from the atmosphere and consequently determining its lifetime and atmospheric burden and affecting vertical profiles of number and mass concentration.…”
mentioning
confidence: 92%
“…Figure 7 shows an example ofĀ on 20 July 2011, which is used as a case study in other BORTAS studies (e.g. Griffin et al, 2013;Franklin et al, 2014). Figure 7a shows longitudinal and latitudinal cross-section views of emissions as they are transported from the Thunder Bay region (50 • N, 88 • W).…”
Section: Tagged Co Model Outputmentioning
confidence: 99%
“…Figure 7a shows longitudinal and latitudinal cross-section views of emissions as they are transported from the Thunder Bay region (50 • N, 88 • W). By the time the plume is observed on 20 July by ground-based observatories over Toronto (43.70 • N, 69.40 • W) (Griffin et al, 2013) and Halifax (44.6 • N, 63.59 • W) (Franklin et al, 2014) the plume is approximately 5-7 days old, corresponding to an emission on 14-15 July. Figure 7b shows that the transported air, intercepted at 63 • W, is composed of a young plume (4-5 days old) surrounded by older air (7 days old) over 47-55 • N. Previous BORTAS-B studies have used the NOAA HYbrid Single-Particle Lagrangian Integrated Trajectory (HYS-PLIT) model (Draxler and Hess, 1998), driven by meteorological reanalyses data from the National Center for Environmental Prediction (NCEP) Global Data Assimilation Program (GDAS) to interpret ground-based remote-sensing data collected during BORTAS-B (Griffin et al, 2013;Franklin et al, 2014).…”
Section: Tagged Co Model Outputmentioning
confidence: 99%